Analisis Peraturan Otoritas Jasa Keuangan Nomor 14 Tahun 2023 Tentang Perdagangan Karbon Melalui Bursa Karbon (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research analyzes the Financial Services Authority Regulation Number 14 of 2023 concerning Carbon Trading through the Carbon Exchange, particularly related to the implementation of the principle of efficiency in reducing greenhouse gas emissions. The methodology employed is normative research with legislative, conceptual, and comparative approaches, along with the analysis of primary and secondary legal materials through literature study and syllogistic methods. The findings indicate that the principles of good legislative regulation and the principle of legality have not been optimally implemented, hindering the efficiency of carbon trading. Identified obstacles include the type, hierarchy, and substance of the regulation, the institutional framework governing carbon trading, and contradictions within the regulation. The research recommends that carbon trading be regulated under a specific law with a dedicated body focusing on this issue, along with adherence to the principles of good legislative formation. The author advises the government, through the Ministry of Environment and Forestry and the Financial Services Authority, to review carbon trading regulations, optimize the authority of the governing body, and ensure that the principle of efficiency is fulfilled.